Introduction to computer graphics : using Java 2D and 3D - Klawonn, Frank (London ; New York : Springer, 2012)
This book provides an introduction to the basic concepts of computer graphics. It couples the technical background and theory immediately with practical examples and applications. The reader can follow up the theory and then see the theory at work in example programs
1. Introduction -- 2. Basic principles of two-dimensional graphics -- 3. Drawing lines and curves -- 4. Areas, text and colours -- 5. Basic principles of three-dimensional graphics -- 6. Modelling three-dimensional objects -- 7. Visible surface determination -- 8. Illumination and shading -- 9. Special effects and virtual reality
Includes bibliographical references and index
Keywords: Computer graphics; Computer science; Computer vision; Java (Computer program language)